Issues And Challenges Of Halal Implementation In Food Industry In Malaysia - Asnidar Hanim Yusuf; Syadiyah Abdul Shukor; Ummi Salwa Ahmad Bustamam (Institute of Research Engineers and Doctors, 2024)
Non-Indexed Publication